The effect of seminal plasma β-NGF on follicular fluid hormone concentration and gene expression of steroidogenic enzymes in llama granulosa cells - Ximena P. Valderrama; Jose F. Goicochea; Mauricio E. Silva; Marcelo H. Ratto (Reproductive Biology and Endocrinology, 2019)
Abstract Background Nerve growth factor (β-NGF) from llama seminal plasma has been described as a potent ovulatory and luteotrophic molecule after intramuscular or intrauterine infusion in llamas and alpacas. We tested the hypothesis that systemic administration of purified β-Nerve Growth Factor (β-NGF) during the preovulatory stage will up-regulate steroidogenic enzymes and Vascular Endothelial Growth Factor (VEGF) gene expression in granulosa cells inducing a change in the progesterone/estradiol ratio in the follicular fluid in llamas. Methods Experiment I: Female llamas (n = 64) were randomly assigned to receive an intramuscular administration of: a) 50 μg gonadorelin acetate (GnRH, Ovalyse, Pfizer Chile SA, Santiago, Chile, n = 16), b) 1.0 mg of purified llama β-NGF (n = 16), or c) 1 ml phosphate buffered saline (PBS, negative control group, n = 16). An additional group of llamas (n = 16) were mated with a fertile male. Follicular fluid and granulosa cells were collected from the preovulatory follicle at 10 or 20 h after treatment (Time 0 = administration of treatment, n = 8/treatment/time point) to determine progesterone/estradiol concentration and steroidogenic enzymes and VEGF gene expression at both time points. Experiment II: Granulosa cells were collected from preovulatory follicles from llamas (n = 24) using ultrasound-guided transvaginal follicle aspiration for in vitro culture to determine mRNA relative expression of Steroidogenic Acute Regulatory Protein (StAR) and VEGF at 10 or 20 h (n = 4 replicates) and progesterone secretion at 48 h (n = 4 replicates) after LH or β-NGF treatment. Results Experiment I: There was a significant increase in the progesterone/estradiol ratio in mated llamas or treated with GnRH or purified β-NGF. There was a significant downregulation in the mRNA expression of Aromatase (CYP19A1/P450 Arom) for both time points in llamas mated or treated with GnRH or llama purified β-NGF with respect to the control group. All treatments except β-NGF (20 h) significantly up regulated the mRNA expression of 3-beta-hydroxysteroid dehydrogenase (HSD3B) whereas the expression of StAR and Side-Chain cleavage enzyme (CYP11A1/P450scc) where significantly up regulated only by mating (20 h), or β-NGF at 10 or 20 h after treatment. VEGF was up regulated only in those llamas submitted to mating (10 h) or treated with purified β-NGF (10 and 20 h). Experiment II: Only β-NGF treatment induced an increase of mRNA abundance of StAR from llama granulosa cells at 20 h of in vitro culture. There was a significant increase on mRNA abundance of VEGF at 10 and 20 h of in vitro culture from granulosa cells treated with β-NGF whereas LH treatment increases VEGF mRNA abundance only at 20 h of in vitro culture. In addition, there was a significant increase on progesterone secretion from llama granulosa cells 48 h after LH or β-NGF treatment. Conclusions Systemic administration of purified β-NGF from llama seminal fluid induced a rapid shift from estradiol to progesterone production in the preovulatory follicle. Differences in gene expression patterns of steroidogenic enzymes between GnRH and mated or β-NGF-treated llamas suggest local effects of seminal components on the preovulatory follicle.